2017
DOI: 10.1016/j.rbmo.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pregnancy rates after reproductive surgery

Abstract: With the development of IVF procedures, the role of reproductive surgery in the management of infertile couples has been questioned. Pregnancy rates (PR) after IVF procedures are well known, but recent data on spontaneous PR after reproductive surgery are scarce. This study aimed to prospectively evaluate how often fertility is restored by reproductive surgery and to identify which independent factors influence spontaneous pregnancy after reproductive surgery. Eight hundred eighty-eight infertile women who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…They also reported that SPs mostly occurred in 2-4 years of successful or unsuccessful IVF attempts (11). Similar to our findings, another study determined that the younger women and also shorter duration of infertility had higher rate of spontaneous pregnancy after surgery (12). Another study showed that SP occurred after the management of autoimmune disorders (13).…”
Section: Discussionsupporting
confidence: 89%
“…They also reported that SPs mostly occurred in 2-4 years of successful or unsuccessful IVF attempts (11). Similar to our findings, another study determined that the younger women and also shorter duration of infertility had higher rate of spontaneous pregnancy after surgery (12). Another study showed that SP occurred after the management of autoimmune disorders (13).…”
Section: Discussionsupporting
confidence: 89%
“…Still, there are few reports on an outcome of spontaneous conception after reproductive surgery due to an opinion that reproductive surgery should only be performed as an initial part of infertility treatment before proceeding to IVF/ICSI 9 . Nevertheless, encouraging reports on a high spontaneous pregnancy rate after reproductive surgery, as in this study, emerged in the last years 8,10 . Similar to our finding, Boyle et al 8 have found the low preterm delivery rate in women who conceived spontaneously after restorative reproductive medicine after failed IVF.…”
Section: Discussionsupporting
confidence: 54%
“…The data included in databases are collected during the hospital stay by attending doctors, nurses, and midwives. The Computerized database of reproductive surgery was described in detail elsewhere (10). The NRART was introduced in 1983 at the Ministry of Health of Republic of Slovenia, and from 1999 the data are also sent to the IVF Monitoring (EIM) Consortium of the European Society of Human Reproduction and Embryology regularly.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations